2xy+4yz +(-3yx)+(-3yz)=
Answers
Answered by
1
Answer:
2xy+4yz+5xy+3yz−6xy
The simplified form of the given expression is calculated as follows
2xy+4yz+5xy+3yz−6xy=2xy+5xy−6xy+4yz+3yz
=xy+7yz
Therefore, 2xy+4yz+5xy+3yz−6xy
=xy+7yz
Step-by-step explanation:
hlo
good morning
Attachments:
![](https://hi-static.z-dn.net/files/d46/43e462687893e6f46ce8c7d3fac63260.jpg)
Answered by
2
Step-by-step explanation:
2xy + 4yz - 3yz - 3yz (as, +*– = –)
= 2xy + 4yz - 6yz. (as, –*– = +)
= 2xy – 2yz (answer)
Similar questions